2019
DOI: 10.1002/lrh2.10200
|View full text |Cite
|
Sign up to set email alerts
|

Commercial use of health data—A public “trial” by citizens' jury

Abstract: IntroductionSurveys suggest a dichotomy in how citizens view research for public benefit and research for commercial gain. Therefore, a research initiative, such as a learning health system, which works for both public and commercial benefit, may be controversial and lower public trust.MethodsThis study aimed to investigate what informed citizens considered to be appropriate uses of health data in a learning health system and why they made those decisions. Two‐paired 4‐day juries were run, with different juror… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 21 publications
0
31
0
Order By: Relevance
“…Previous studies have shown how responses to care.data on Twitter attracted critical commentary [31], including from interest communities in politics, health care, and the media [32]. Before the observation period examined in this study, concerns had been raised about access to patient data by commercial companies, especially where these uses were perceived to be primarily motivated by profit rather than public benefit [30,[33][34][35]. This study contrasts with these findings, showing how #datasaveslives was used in the wake of public backlash to care.data to spread mainly positive messages about data use and reuse, and to increase transparency, demonstrate solidarity, and provide supportive networks among health, data, and IT professionals.…”
Section: Comparisons With Previous Workmentioning
confidence: 99%
“…Previous studies have shown how responses to care.data on Twitter attracted critical commentary [31], including from interest communities in politics, health care, and the media [32]. Before the observation period examined in this study, concerns had been raised about access to patient data by commercial companies, especially where these uses were perceived to be primarily motivated by profit rather than public benefit [30,[33][34][35]. This study contrasts with these findings, showing how #datasaveslives was used in the wake of public backlash to care.data to spread mainly positive messages about data use and reuse, and to increase transparency, demonstrate solidarity, and provide supportive networks among health, data, and IT professionals.…”
Section: Comparisons With Previous Workmentioning
confidence: 99%
“…A public consultation by Ipsos MORI [ 24 ] on behalf of the UK Medical Research Council regarding the use of personal health information in research found that 70% of participants agreed the advantages of medical research – which the authors say are mainly considered ‘societal’ – outweigh the disadvantages (mainly seen as the disclosure of personal health information). Study participants have been found to consider financial profit an unacceptable motive for the use of administrative data [ 25 27 ]. A 2014 study by Marion Oswald investigating attitudes towards sharing personal data with the public sector [ 27 ] found most participants would be comfortable with their data being used to improve public services, but only 23% were comfortable with it being used by the NHS, and 27% by central government, to make profits to fund services.…”
Section: Methodsmentioning
confidence: 99%
“…Some study participants have also identified public benefits of private companies having access to data in certain circumstances; in such cases, there has been a preference for greater safeguards and controls than might be expected for public bodies [ 18 , 25 ]. Aitken et al [ 18 ] found that, although some organisations are trusted more than others, this does not mean access to data by these groups is automatically supported, and vice versa.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“… 6 , 7 , 8 , 9 , 10 , 11 However, even with protections in place, a number of studies also show that community members remain concerned about data security, the potential for misuse of their data and their lack of control over their own health information. 6 , 7 , 8 , 9 , 10 , 11 , 12 These studies also show that this disquiet is heightened if private sector organizations have access to the data and that the use of such data for financial gain is an additional significant concern. 6 , 7 , 8 …”
Section: Introductionmentioning
confidence: 94%